ANALISIS KINERJA KEUANGAN DALAM MENENTUKAN NILAI PERUSAHAAN PADA SEKTOR ENERGI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Angel Yosefin Elisabeth Simanjorang (2022)
The purpose of this study is to determine the effect of company performance as proxied by Return on Assets (ROA), Current Ratio (CR), and Debt to Equity Ratio (DER) in determining firm value which also proxied by price book value (PBV) in the energy sector listed on the Indonesia Stock Exchange in 2017-2019. This research is a quantitative research. The population used in this study is energy-sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2017-2019. The sampling technique used was probability sampling, where 38 companies were selected as research samples in a period of three years and 114 research sample units were obtained. Data analysis used E-Views version 12 and Microsoft Excel 2013 with a significance level of 5%. The results obtained from data processing are that profitability (ROA), liquidity (CR), and solvency (DER) has no effect on the company value.